Compatibility and stability of valsartan in a solid pharmaceutical formulation - Tamíris Amanda Júlio; Igor Fernando Zâmara; Jerusa Simone Garcia; Marcello Garcia Trevisan (Universidade de São Paulo, 2013)
Valsartan (VAL) is a highly selective blocker of the angiotensin II receptor that has been widely used in the treatment of hypertension. Active pharmaceutical ingredient compatibility with excipients (crospovidone, hypromellose, magnesium stearate, microcrystalline cellulose and titanium dioxide) is usually evaluated in solid pharmaceutical development. Compatibility and stability can be evaluated by liquid chromatography. Studies were performed using binary mixtures of 1:1 (w/w) VAL/excipient; samples were stored under accelerated stability test conditions (40 ºC at 75% relative humidity). The results indicate that VAL is incompatible with crospovidone and hypromellose, which reduced the VAL content and gave rise to new peaks in the chromatogram due to degradation products.